Mutated regions of nucleophosmin 1 elicit both CD4+ and CD8+ T-cell responses in patients with acute myeloid leukemia - Greiner, Jochen; Hofmann, Susanne; Schmitt, Anita; Schmitt, Michael (Blood, 2012)
Mutations in the nucleophosmin gene (NPM1mut) are one of the most frequent molecular alterations in acute myeloid leukemia (AML), and immune responses may contribute to the favorable prognosis of AML patients with NPM1mut. In the present study, we were able to demonstrate both CD4+ and CD8+ T-cell responses against NPM1mut. Ten peptides derived from wild-type NPM1 and NPM1mut were subjected to ELISPOT analysis in 33 healthy volunteers and 27 AML patients. Tetramer assays against the most interesting epitopes were performed and Cr51-release assays were used to show the cytotoxicity of peptide-specific T cells. Moreover, HLA-DR-binding epitopes were used to test the role of CD4+ T cells in NPM1 immunogenicity. Two epitopes (epitopes #1 and #3) derived from NPM1mut induced CD8+ T-cell responses. A total of 33% of the NPM1mut AML patients showed immune responses against epitope #1 and 44% against epitope #3. Specific lysis of leukemic blasts was detected. To obtain robust immune responses against tumor cells, the activation of CD4+ T cells is crucial. Therefore, overlapping (OL) peptides were analyzed in ELISPOT assays and OL8 was able to activate both CD8+ and CD4+ T cells. The results of the present study show that NPM1mut induces specific T-cell responses of CD4+ and CD8+ T cells and therefore is a promising target for specific immunotherapies in AML.
Gesehen am 11.05.2018